2015
DOI: 10.1890/14-2096.1
|View full text |Cite
|
Sign up to set email alerts
|

Life history differences influence the impacts of drought on two pond‐breeding salamanders

Abstract: Drought is a strong density-independent environmental filter that contributes to population regulation and other ecological processes. Not all species respond similarly to drought, and the overall impacts can vary depending on life histories. Such differences can necessitate management strategies that incorporate information on individual species to maximize conservation success. We report the effects of a short-term drought on occupancy and reproductive success of two pond-breeding salamanders that differ in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 59 publications
2
37
0
1
Order By: Relevance
“…Babbitt et al 2003;Babbitt 2005;Anderson et al 2015). The actual number of drying and filling events, as well the actual length of days a wetland holds water can be predicted using our methods, which will improve our understanding of the sensitivity of different species to temporal regimes of inundation.…”
Section: Discussionmentioning
confidence: 96%
“…Babbitt et al 2003;Babbitt 2005;Anderson et al 2015). The actual number of drying and filling events, as well the actual length of days a wetland holds water can be predicted using our methods, which will improve our understanding of the sensitivity of different species to temporal regimes of inundation.…”
Section: Discussionmentioning
confidence: 96%
“…Our analyses found that colonisation more frequently results in effective breeding in plastic containers than in other waterbodies. Yet such a strategy results in frequent breeding failure (Anderson et al, 2015;Green et al, 2013;Hartel et al, 2011). Moreover, inter-annual abandonment of a waterbody by breeding adults is lower in plastic containers than in other waterbodies.…”
Section: Influence Of the Hydroperiod On The Movement Behaviour Of mentioning
confidence: 99%
“…Altermatt & Ebert, 2008, 2010Bates, Sadler, & Fowles, 2006). In these organisms, breeding success is strongly impacted by waterbody desiccation and intraspecific competition at the larval stage (Anderson, Ousterhout, Peterman, Drake, & Semlitsch, 2015;Green, Hooten, Grant, & Bailey, 2013;Hartel, Bancila, & Cogalniceanu, 2011;Van Buskirk & Smith, 1991;Wilbur, 1976). Pond-breeding amphibians are excellent biological models to fill this gap.…”
mentioning
confidence: 99%
“…At each site, each year, we conducted 3 independent dip net surveys, and typically 3 trapping sessions (ponds surveyed = 139, 169, and 151 in 2012, 2013, and 2014, respectively), although we excluded some sites from trapping because of their location (e.g., roadbed ditch) or shallow water depth ( n = 18, 24, and 31 in 2012, 2013, and 2014, respectively). Previous analyses with these data reported that detection did not vary by sampling method (Peterman et al , Anderson et al ). We therefore included all sites surveyed in analyses regardless of whether we used funnel traps.…”
Section: Methodsmentioning
confidence: 55%
“…The reasons for ringed salamanders failing to breed in nearly half of the wetlands in the Focal Area are varied, and are unknown in many cases. The presence of fish and short or ephemeral hydroperiods are 2 of the primary reasons that ringed salamanders fail to breed or successfully recruit from a pond (Peterman et al , Anderson et al , Semlitsch et al ), both of which can be modified through direct management (Walston and Mullin , Calhoun et al ). It is important, however, to carefully assess all relevant structural habitat features to ensure that restoration efforts provide more than partial remediation.…”
Section: Discussionmentioning
confidence: 99%